Angular for Java developers. (Manning Publications, 2020)
"In Angular for Java Developers part three: Building a real site you'll work hands-on to create a fully responsive, functioning front-end application using Angular. All examples are related to the kind of Java development you're familiar with, making it easy to expand your skills. In the third of a running series of five courses, you'll learn how to incorporate resources like Bootstrap, and how to use template and reactive forms."--Resource description page